Perancangan Sistem Pengolaan dan Penagihan Piutang Mitra Usaha pada Bandar Udara Kertajati Dengan Menggunakan Metode Waterfall - Annisa Permatasari Nugraha; Endang Chumaidiyah; Yudha Prambudia (IAI Nasional Laa Roiba Bogor, 2024)
Husein Sastranegara Airport has problems with the management of receivables for its business partners with three problem factors, namely confirmation of payment of receivables that takes a long time, collection of receivables that is still manual, and bad debts occur. At Husein Sastranegara Airport there will be an operational transfer to Kertajati Airport. To avoid similar problems, it is necessary to find a solution for managing trade receivables for the sake of company sustainability and growth. With the existing problems and limitations, a system for managing and collecting trade receivables is designed, with the existence of This system can help companies to manage their receivables and help business partner owners monitor their business bills so that they can increase efficiency and effectiveness in billing and managing their receivables. Information system development uses the Waterfall method approach with stages of software requirements analysis, design, program code creation, testing, and support or maintenance. The features for the receivables management and collection system consist of business partners, access, invoices, payments, warning letters, reports and profiles. Based on the analysis carried out, the results showed that the difference in invoice issuance process cycle time was 6.33 hours and the efficiency increase was 3.86%, then the billing process cycle time difference was 9.91 hours and the efficiency increase was 13.14%, as well as the difference in processing time. payment of 18.8 hours and additional efficiency of 8.39%. Finally, the difference in reporting process time was 10.17 hours and the efficiency increase was 3.32%. The usability test was also carried out using the System Usability Score (SUS) showing a score of 73.06 which is in the acceptable category.